Comparison of shear bond strength of silorane and methacrylate-based composites to IPS empress 2 ceramic with various surface treatments - Akbarian, Sahar; Lesani, Mina; Koohpeimaa, Fatemeh (Journal of Dental School, 2019)
Objectives Treatment of chipped or fractured porcelain with composite resin is considered as an economic treatment for minor fractures in ceramics. The aim of this study was to evaluate the effect of different ceramic surface treatments on bond strength of methacrylate-based and silorane-based composite resin to IPS Empress 2. Methods Sixty IPS Empress 2 ceramic discs were fabricated and after etching with 9.6% hydrofluoric acid, they were divided into six groups: (1) P90 primer and bonding agent + Filtek P90 composite resin; (2) Single Bond + Filtek Z250 composite resin; (3) similar to the first group + silane pretreatment; (4) similar to the second group + silane pretreatment; (5) silane pretreatment + Filtek P90 composite resin; (6) silane pretreatment + Filtek Z250 composite resin. Each specimen was subjected to shear load until fracture occurred. Statistical analysis was performed using one-way ANOVA, Tukey’s test and t-test. Results Regardless of the type of surface treatment, Z250 composite demonstrated significantly higher shear bond strength than P90 composite (P < 0.05). Group 4 showed the highest shear bond strength values with statistically significant difference with other groups while the fifth group showed the least values (P < 0.05). Conclusion Silane coating along with the application of adhesive system and etching in methacrylate-based composite was the most efficient surface treatment in terms of bond strength.